Evaluation of Herbal Honey with Black Cumin and Curcuma xanthorriza as an Antioxidant Supplement for Stunting Prevention - Lukman Hardia; Akrom Akrom; Titiek Hidayati; Nanik Sulistyani (Journal of Public Health and Pharmacy, 2025)
Introduction: Honey has been widely used as a nutritional supplement and medicine. Many herbal honey products are developed as nutritional supplements that are combined with SFM to make them more effective, but there are still many shortcomings due to the unpleasant taste produced, unattractive physical appearance, and high susceptibility to oxidation reactions that cause severe damage to the quality of honey, especially in the content of active substances, viscosity, and pH, which can cause the effectiveness of honey to decrease and result in product failure as nutritional supplements to treat stunting problems. We have developed an herbal honey multi-nutrient supplement that combines honey with black cumin oil and Curcuma xanthorriza extract called HBCX. Adding Curcuma xanthorriza extract and black cumin oil to honey is expected to increase honey's benefits as an antioxidant. This study aims to determine the physicochemical characteristics (pH and viscosity), heavy metal contamination content, polyphenols, and antioxidant activity. Methods: This experimental laboratory research was conducted at the Pharmacy Lab, Faculty of Pharmacy, UAD. The viscosity and pH of HBCX were observed using an Ostwald viscometer and a pH meter. Total phenol determined by Folin-Ciocalteau reagent and gallic acid standard. Determination of antioxidant activity using the DPPH method. The data are presented in a quantitative descriptive manner and matched with the SNI honey standard. Results: The results showed that HBCX herbal honey had a higher viscosity than the sampled honey from the market but was still lower than the SNI requirements. HBCX honey has a lower pH than sample honey products from the market but still complies with national standards. HBCX honey is safe from heavy metal contamination and contains polyphenols. The antioxidant activity of HBCX honey is relatively high, with IC50=54.78 ppm. Conclusion: HBCX has high polyphenol content, is safe from heavy metal contamination, and has sufficient antioxidant activity.